Complexities of Simultaneously Improving Quality and Lowering Costs in Hospitals; Comment on "Hospitals Bending the Cost Curve With Increased Quality: A Scoping Review Into Integrated Hospital Strategies" - Dinesh R. Pai (Kerman University of Medical Sciences, 2023)
As health systems transition to value-based care delivery models, reducing costs and improving quality of care without sacrificing either remains a challenge for many healthcare organizations. There is extensive research on hospital costs, however, works addressing the complex relationship between hospital costs and the quality of care have been limited. In this commentary, I expound on the scoping review on integrated hospital strategies by Wackers et al that aim to improve quality while lowering costs. Specifically, I reiterate the complexity of the relationship between cost and quality and delve into major interdependent themes identified by the authors as relevant for the implementation of hospitals' integrated strategy.